Duration of works, flight hours, and blood pressure related to noise-induced hearing loss among Indonesian Air Force helicopter pilots (Medical Journal of Indonesia, 2006)
Helicopter pilots exposed to high intensity noise and other risk factors had increased risk to be noise-induced hearing loss (NIHL). Therefore, it is beneficial to study several risk factors related to NIHL. This study was a nested case-control. Data was extracted from available medical records among helicopter pilots who performed routine aerophysiology training indoctrination (ILA) during 1980 through March 2004 at Saryanto Institute for Aviation and Aerospace Medicine (Lakespra), Jakarta. Case was those who had audiogram with a notch of 40 dB or more and of 4000 Hertz on one site or bilateral ears. A case was matched by two controls who free from NIHL up to 2004. All risk factors for cases and controls were counted as of reference date of cases diagnosed. There were 187 medical records available for this study. A number of 32 cases and 64 controls were identified. The final model reveals that NIHL was related to total duration of works, flight hours, and blood pressure. Those who had 500 hours or more than less 500 hours had a moderate increased risk for 2.5 to be NIHL [Adjusted odds ratio (ORa)= 2.50; 95% confidence intervals (CI) = 0.66-9.29; p = 0.180]. Those who had total duration works 11-24 years had a moderate increased to be NIHL for 2.7 times (ORa = 2.71; 95% CI=0.90-8.10; p = 0.075). Furthermore, prehypertension and hypertension stage 1 subjects than normal blood pressure had moderate trend increased risk to be NIHL. In conclusion total flight hours for 500 hours or more, total duration works 11-24 years, or prehypertension and hypertension stage 1 increased risk NIHL. (Med J Indones 2006; 15:185-90) Keywords: noise induced hearing loss, flight hours, working duration, blood pressure